Mechanically robust honeycomb graphene aerogel multifunctional polymer composites - Zhang, Qiangqiang; Xu, Xiang; Li, Hui; Xiong, Guoping; Hu, Han; Fisher, Timothy S. (Carbon (New York), 2015)
This work reports the fabrication and characterization of three-dimensional (3D) graphene aerogel (GA)–polydimethylsiloxane (PDMS) composites (GAPC) with outstanding mechanical, electrical and thermal properties. GAPC was fabricated by impregnating 3D GA frameworks with PDMS via ice-bath-assisted infiltration and vacuum curing processes. Because of the well-interconnected 3D GA frameworks, GAPC exhibits extremely large deformability (compressive strain=80% and tensile strain=90%), high electrical and thermal conductivities (1S/cm and 0.68W/(mK), respectively), a stable piezo-resistance effect, rapid electric Joule heating performance ((dT/dt)max>3°C/s under a heating power of 12W/cm3), and high hydrophobicity (contact angle=135°). Furthermore, GAPC exhibits a negative temperature coefficient of expansion with decreased electrical resistivity over a broad temperature range, indicating a typical semiconducting behavior and a dual two-dimensional/3D hopping conduction mechanism.